Flower arranging : 290 projects for fresh and dried bouquets, garlands and posies - Barnett, Fiona. 4 0 16; Moore, Terrence; 5 (Wigston, Leicestershire, England : Lorenz Books, 2012)
A guide to making decorative displays from fresh and dried flowers. It presents over 290 projects including how to make exquisite posies, pomanders, swags, wreaths, centrepieces and bouquets, shown in over 1700 colour photographs.
Includes index.;Previously published as two separate volumes, The new flower arranger and New flower design -- T.p. verso.
Adult;Adult.
Keywords: 2 -- 0; 6; Flower arrangement.;Floral decoration.;Dried flower arrangement; 20; 2